Femoral nerve block for pain relief in hip fracture: a dose finding study1. (24th May 2014) - Watson, M. J.; Walker, E.; Rowell, S.; Halliday, S.; Lumsden, M. A.; Higgins, M.; Binning, A.; McConnachie, A.
Summary Hip fracture is the most common orthopaedic emergency. We investigated the concentration of 30 ml levobupivacaine that provided analgesia to 50% and 95% of patients with a hip fracture when injected around the femoral nerve under ultrasound guidance. We defined analgesia as a ≥ 20‐point decrease on a 100‐point pain scale with reduced cold sensation in the middle third of the anterior thigh 30 min after the nerve block. We increased the concentration of levobupivacaine if the preceding dose had been ineffective and decreased it if the preceding dose had been effective. Probit regression modelling estimated the effective (95% CI) concentration of 30 ml levobupivacaine in 50% and 95% of patients with a fractured hip to be 0.026 (0.023–0.028)% w/v and 0.036 (0.027–0.047)% w/v, respectively.